In vitro evaluation of coenzyme Q10 on primary fibroblast culture - Herawati, Dahlia (Majalah Kedokteran Gigi Indonesia, 2023)
Chronic inflammation in periodontitis results in continuous production of Reactive Oxygen Species (ROS), so the levels are excessive, causing destruction of the gingiva, periodontal ligament, and alveolar bone through a variety of mechanisms including DNA damage and the formation of proinflammatory cytokine. One way to prevent periodontal tissue damage caused by excessive ROS formation is by administering antioxidants. Coenzyme Q10 is a powerful antioxidant that is beneficial for inhibiting free radicals to prevent the progression of periodontal tissue destruction and accelerate healing processes. The purpose of this study was to evaluate the fibroblast proliferation of the combination of Coenzyme Q10 and vegetable glycerin compared to PerioQ. Materials used were made of original Coenzyme Q10 dissolved in glycerin that was prepared in a ratio of 2:8 and 1:9, and Perio Q as the control. Each group consisted of six samples (n = 6). Primary fibroblasts were derived from healthy gingival tissue. Observations on day-1, -3, and -5 using MTT assay at a wavelength of 550nm. Statistical analysis used a Two-Way ANOVA test followed by a Post Hoc test.  The experiment showed the absorbance values were high in all the groups, the highest value was on day 3, namely Coenzyme Q10 at a concentration of 2:8, followed by Coenzyme Q10 at a concentration of 1:9, and PerioQ. The statistical tests showed significant differences in the 3 groups (p < 0.05). It is concluded that Coenzyme Q10 in 1:9 and 2:8 concentrations were both as viable as Perio Q towards primary gingival fibroblast culture.